Anxiety and Spatial Navigation in Williams Syndrome and Down Syndrome. Issue 3 (3rd April 2022) - Farran, Emily K.; Hudson, Kerry D.; Bennett, Amelia; Ameen, Aan; Misheva, Iliana; Bechlem, Badri; Blades, Mark; Courbois, Yannick
ABSTRACT: Individuals with Down Syndrome (DS) and individuals with Williams syndrome (WS) present with poor navigation and elevated anxiety. The aim of this study was to determine the relationship between these two characteristics. Parent report questionnaires measured navigation abilities and anxiety in WS (N = 55) and DS (N = 42) as follows. Anxiety: Spence Children's Anxiety Scale and a novel measure of navigation anxiety. Navigation: Santa Barbara Sense of Direction Scale (SBSOD) and a novel measure of navigation competence. Most individuals were not permitted to travel independently. A relationship between navigation anxiety and SBSOD scores (but not navigation competence) was observed for both groups.